ANALISA KEBIJAKAN PERMENDIKNAS No. 69 Tahun 2009 TENTANG STANDAR PEMBIAYAAN PENDIDIKAN - Haris, Abdul (Inovasi: Jurnal Diklat Keagamaan, 2016)
Education process needs costs. Problems of education financing arestill struggling on the sources of the cost of education, managementeducation costs, and the allocation of the cost of education, as wellas the cost-efficiency of education. The policy of Permendiknas 69 /2009 is a policy that answer education financing. The policy wasstudied through formul ati on anal ysi s, Material /Content,Implementation and Evaluation. The fact suggests that Permendiknas69 / 2009, regulates the costs operating that only lasted for one year,for year 2009 Using the DKI Jakarta bases. It does not regulatei nvestment costs, and personnel costs yet. Therefore, thedetermination of costs every year is needed, and preferably beforethe new school year.